IRISS (Increasing Resilience in Surveillance Societies) FP7 European Research Project, Deliverable 3.2: Surveillance Impact Report - Ball, Kirstie (2014)
External research report produced for the European Commission as part of the FP7 IRISS project: Increasing Resilience in Surveillance Socieities, containing European case studies on the varying formats of neighbourhood watch, including the cultural and historical factors which may influence the creation of neighbourhood watch groups in the first instance. Overview of neighbourhood watch in the United Kingdom and analysis of the changing role of the police in relation to community policing and the impact which this has had on the primary purpose of neighbourhood watch organisations.This deliverable was written as part of the IRISS project which received funding from the European Union’s Seventh Framework Programme for research, technological development and demonstration under Grant Agreement No. 285593. Additional co-authors: Alessia Ceresa, Chiara Fonio, Walter Peissl, Robert Rothman, Jaro Sterbik Lamina, Ivan Szekely, Beatrix Vissy, Wolfgang Bonß, Daniel Fischer, Gemma Galdon Clavell, Reinhard Kreissl, Alexander Neumann, Nils Zurawsk